Comparative Analysis of Energy Productivity Used to Manage Waste With Comparison of Pelet Outputs in Electricity in STT-PLN Jakarta - Pawenary Pawenary; Supriadi Legino; Mega Cintya (DINASTI RESEARCH, 2020)
In STT-PLN environment each day has the potential to produce 875 kg of waste per day, based on this value it can be used as a waste pellet of 43.5 kg per day. STT-PLN Jakarta Electricity Jakarta launched the Local Waste Management Method (TOSS) with this method, STT-PLN is able to manage its own waste which is expected to be a solution for the utilization of waste into fuel. The machines used are hammer mill and chopper machine with 22 kW of power and operated for 3 hours, worth Rp.193,680.96 per day. Pellet production is used as fuel which can be distributed to PLTSa, Biomass Power Plants and pellet stoves. Based on the results of the calculation of the economic analysis obtained is NVP of IDR 454,007,469.00, IRR 26,855% and PBP 4,84 years, STT-PLN Jakarta Electricity is feasible to be continued.